Lymphatics of the lungs - Ruiz Liard, Alfredo (Cirugía del Uruguay, 1982)
A brief historical reference is given. Accorcling to Rouviere and Dyon the Lymphatics of the lung are divided in 4 groups. Subcarinal lymph nades is a very important group since it receives lymphatic drainage of ali lung through Borrie's lymphatic sump. Besides it sends efferents to both paratracheal nades. The paratracheal lymph nade receives lymphatic flow from the homolateral as well as the opposite side through the subcarinal groups. The peripherical mediastinal lymph nades (anterior and posterior) draw the lympha of upper lobes specially towads left. The internal mammary lymph nades :receives the lymphatic lung flow mainly from the upper side. There is an important connection between the different groups. Finally the high connections as well as the low ones link the lymphatics of the lung with the cervical and abdominal lymph nodes.